STUDI METODE PENGGANTIAN RELAI MEKANIS MENJADI ELEKTRIS PANEL TEGANGAN MENENGAH PLTU UNIT 4 MUARA KARANG - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
Protective Relay is a device that provides alarm and trip / open signals to circuit breakers due to interference with protected equipment. Replacement of protection relay at the switchgear location of PLTU unit 4 Muara karang has been planned since 2010 and realized in December 2016 this coincides with Over Houl Mean Inspection. There are several problems encountered in the replacement of switchgear protection relays. The problem faced in performing this switchgear protective relay replacement is on mechanical relays that are replaced into electrical relays requiring many modifications and work steps. So in conducting this research is needed a proper method of research in order to produce a system of protection that is feasible operation